Degradation of Brilliant Blue Dye (FCF) in Wastewater Using Visible Light Induced Activity of α-Haematite Nanoparticle Synthesized via Green Route - Emmanuel Ba’aku AttahDaniel; Emmanuel A Kamba; Mohammad Ziyaulhaq Mohammad; James Dama Habila (Kwaghe International Journal of Sciences and Technology, 2026)
This study investigated the photocatalytic activity of α-Fe2O3 nanoparticles (hematite) synthesized from the extract of Senna siamea flower and characterized using Transmission Electron Microscopy (TEM), Thermogravimetric Analysis / Differential Thermal Analysis (TGA/DTA), Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray (EDX) Analysis. The photocatalytic activity of the α-Fe2O3 nanoparticles was measured by degradation of Brilliant Blue Dye. The α-Fe2O3-S.S nanoparticles showed excellent photocatalytic performance, an optimum photocatalytic degradation 82% was obtained within 150 minutes intervals at loading catalyst dose of 150 mg at a concentration of 15 ppm. Thus, the catalyst demonstrated efficient degradation capacity of Brilliant Blue dye in wastewater.